Analisis Alokasi Dana Corporate Social Responsibility - Tsani Rafif; Wahid Naja (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Responsibility (CSR) or corporate social responsibility, the definition of which is still a matter of debate among practitioners and academics. As a concept that originates from abroad, the main challenge is to provide a meaning that is appropriate to the Indonesian context. More precisely, before implementing CSR, it should be adapted to local situations and conditions in Indonesia. This will really help the implementation of CSR so that it is not misused, especially in advancing the quality of human life in Indonesia.